2019
DOI: 10.31234/osf.io/2uxej
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of structural priming in contact-induced change: Subject pronoun expression in L1 Turkish by Turkish-Dutch bilinguals

Abstract: Subject pronoun expression has been extensively studied for effects of language contact, but it is fairly recent that these studies started including cross-language structural priming paradigms. The earlier studies on subject pronoun use in Turkish spoken by Turkish-Dutch bilinguals did not find any difference from monolingual speakers of Turkish but reported a few instances of unconventional use of subject pronouns, indicating the influence of Dutch on Turkish. This study aimed to determine whether structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(113 reference statements)
1
0
0
Order By: Relevance
“…Given that the first-person subject is always overtly produced in English, this priming across language may well cause these bilinguals to produce overt subjects relatively often in Spanish, potentially leading to a shift in the frequency distributions over overt vs. dropped subject use in this linguistic community. Similar results have recently been found by Sodacı et al (2019) in Turkish-Dutch bilinguals. Dutch is like English in that subject pronouns are always overtly produced, while Turkish is like Spanish in that overt use of subject pronouns is not standard and follows certain pragmatic regularities.…”
Section: Priming and Language Changesupporting
confidence: 91%
“…Given that the first-person subject is always overtly produced in English, this priming across language may well cause these bilinguals to produce overt subjects relatively often in Spanish, potentially leading to a shift in the frequency distributions over overt vs. dropped subject use in this linguistic community. Similar results have recently been found by Sodacı et al (2019) in Turkish-Dutch bilinguals. Dutch is like English in that subject pronouns are always overtly produced, while Turkish is like Spanish in that overt use of subject pronouns is not standard and follows certain pragmatic regularities.…”
Section: Priming and Language Changesupporting
confidence: 91%
“…The diverse coding schemes employed in these studies may well stem from the fact that persever-ation has been shown to happen on various levels of linguistic representation including syntactic, semantic, structural, and lexical (see Pickering & Ferreira 2008for a review, Travis 2007. For example, while lexical repetition appears to boost the strength of perseveration, perseveration also appears to happen between linguistic structures in the absence of lexical repetition (Pickering & Ferreira 2008, Travis 2007) and even when speakers switch between languages (de Prada Pérez 2018, Gries & Kootstra 2017, Sodaci 2018, Torres Cacoullos & Travis 2010.…”
Section: Research On Perseverationmentioning
confidence: 99%